Prevalencia de parásitos intestinales en habitantes de una comunidad rural del estado Bolívar, Venezuela - Devera Rodolfo; Blanco Ytalia; Amaya Iván; Álvarez Eneida; Rojas Jessika; Tutaya Rosario; Velásquez Virma (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Abstract: To determine the prevalence of intestinal parasites in a sample of residents from the rural community, "La Carolina," in the State of Bolivar, Venezuela. Material and Methods: A fecal sample from each participating inhabitant was analyzed using techniques of direct examination, Kato, spontaneous sedimentation and Kinyoun staining. Of the 115 people tested, 97 were parasitized with a prevalence of 84.3 %. With regard to age, all groups were affected equally (c2 = 0.812 df: 6 p > 0.05), although the largest number of cases (52 people) were found in the group of 0-9 years. Both sexes were equally affected (p> 0.05). The study found 54.6% polyparasitism and 45.4% monoparasitism. Nine species of intestinal parasites were diagnosed. The group of protozoa and chromists were more prevalent (94.8%) than helminths. Blastocystis spp. was the most prevalent parasite with 65.2 %. No intestinal coccidia were diagnosed. The most common parasitic associations were between protozoa, emphasizing Blastocystis spp. with Giardia intestinalis (22.6%) and Blastocystis spp. with Endolimax nana (15.1%). An important prevalence of intestinal parasites (84.3%) was determined in the rural community, "La Carolina," State of Bolivar. Resumen: Determinar la prevalencia de parásitos intestinales en una muestra de habitantes de la comunidad rural "La Carolina" del estado Bolívar, Venezuela. Materiales y Métodos: Una muestra fecal de cada habitante participante fue analizada mediante las técnicas de examen directo, Kato, Sedimentación Espontánea y coloración de Kinyoun. Resultados: De los 115 habitantes evaluados, 97 resultaron parasitados para una prevalencia de 84,3%. Con relación a la edad, todos los grupos fueron afectados por igual (c 2 =0,812 g.l.: 6 p>0,05) aunque la mayor cantidad de casos (52 habitantes) se encontraron en el grupo de 0-9 años. Ambos sexos fueron afectados por igual (p>0,05). Se encontró 54,6% de poliparasismo y 45,4% de monoparasitismo. Nueve especies de enteroparásitos fueron diagnosticados, siendo el grupo de los chromistas y protozoarios más prevalentes (94,8%) que los helmintos. Blastocystis spp. fue el parásito más prevalente con 65,2%. No se diagnosticaron coccidios intestinales. Las asociaciones parasitarias más comunes fueron entre protozoarios, destacándose la de Blastocystis spp con Giardia intestinalis (22,6%) y Blastocystis spp. con Endolimax nana (15,1%). Conclusión: Se determinó una importante prevalencia de parásitos intestinales (84,3%) en la comunidad rural "La Carolina" del estado Bolívar, Venezuela.